Enforcement Capacity and the Impact of Labor Regulation : Evidence from the Russian Federation - Gonzalez, Alvaro; Sharma, Siddharth; Subhash, Hari (World Bank, Washington, DC, 2016)
The impact of business regulations on firms could depend on how the regulations are enforced in practice. Exploiting variation in enforcement capacity across the Russian Federation's administrative regions, this paper examines whether the enforcement of restrictive regulations on hiring and firing workers affects how firms adjust employment during industry upswings and downswings. The analysis finds that the extent to which firms adjust employment upward during industry upswings and downward during downswings is smaller in regions with stronger enforcement capacity (or stricter de facto employment protection). The effect of enforcement is sizable: for example, increasing enforcement capacity from the 25th to the 75th percentile dampens employment adjustment in a downswing by 34 percent. Thus, although restrictive regulation on hiring and firing reduces the ability of firms to adjust employment, the extent to which it does so depends on enforcement.